2023
DOI: 10.1088/1361-6528/acf474
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption enhancement in inhomogeneous InGaN nanowire arrays photocathode

Zhihao Cao,
Lei Liu,
Feifei Lu
et al.

Abstract: In the development of surface structures, nanowire arrays (NWAS) have been widely studied because of their trapping effect. In this paper, the finite difference time domain (FDTD) method is used to simulate homogeneous and inhomogeneous NWAS. We studied the influence of the structural parameters of InGaN NWAS and inhomogeneous arrays on optical response properties. The optical response includes light absorptivity and cutoff wavelength sensitivity. The simulation results show that the inhomogeneous NWAS can inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In order to absorb solar energy as high as possible, nanostructures of different shapes have been continuously developed. More and more research results have shown that InGaN nanostructures can achieve higher incident light absorption through antireflection. These are mainly attributed to the trapping effect of nanostructures. , Zhangyang et al used first-principles to calculate the electrical and optical properties of InGaN NWA structures under different In components.…”
Section: Introductionmentioning
confidence: 99%
“…In order to absorb solar energy as high as possible, nanostructures of different shapes have been continuously developed. More and more research results have shown that InGaN nanostructures can achieve higher incident light absorption through antireflection. These are mainly attributed to the trapping effect of nanostructures. , Zhangyang et al used first-principles to calculate the electrical and optical properties of InGaN NWA structures under different In components.…”
Section: Introductionmentioning
confidence: 99%